Considering ethnicity in teaching and learning statistics: should I worry about where my students come from?. Issue 2 (2003) - Nur, Darfiana; Mengersen, Kerrie
Abstract : In the past decade there has been strong interest in the special needs of overseas students attending Australian universities, with respect to teaching and learning. This paper reports on three action research studies that address the question of whether such issues remain in the teaching and learning of statistics in particular.